Metal redistribution during cementation of historic processing residues, Macraes gold mine, New Zealand. Issue 1 (2nd January 2021) - Kerr, Gemma; Craw, Dave
ABSTRACT: Roasted residues from historic gold mine processing at the Golden Point historic reserve were thoroughly cemented by surfical processes. The cements are composed mainly of oxidised and acidic Fe–As–S minerals with varying particle size and crystallinity. Bukovskyite (Fe2 [AsO4 ][SO4 ][OH].7H2 O) and scorodite (FeAsO4 .2H2 O) are the most prominent of these minerals, but a range of As and S bearing ferric iron oxyhydroxide compounds are also abundant, including K-jarosite and schwertmannite. Arsenolite (As2 O3 ) is a minor component, either persisting from original roasting or precipitated via local reduction in the cement. After the historic roasting the residues were treated with liquid Hg to extract gold, and some of that Hg remains in the residues. This Hg now occurs as microcrystalline schuetteite (Hg3 [SO4 ]O2 ), remobilised nano-scale liquid Hg droplets, and as micron-scale Hg-rich layers in ferric iron oxyhydroxide compounds in the cements. Tungsten mobilised from primary ore scheelite is contained in ferric iron oxyhydroxide and as Fe-meymacite (WO3 .xFe2 O3 .nH2 O) in the cements. The cementation processes have effectively confined metals within the residues.